Edukasi Pemasaran Online untuk Usaha Mikro Kecil(UMK) dan Masyarakat Desa - Arum Ardianingsih; Hidayatul Affifah (SULUH: Jurnal Abdimas, 2021)
Micro and small businesses(MSEs) are seen as the businesses that can survive the most economic conditions. Online marketing is needed to increase sales product homemade village community, especially micro and small businesses(MSEs). This service activity aims to educate and provide understanding of online marketing to village community and micro and small business (MSE) entrepreneurs. The dedication method is done through counseling and game fun so that it attracts the audience enthusiastically to the activity until it is finished. The results of the activity showed that the general community of karangtengah village and micro and small businesses (MSEs) in karangtengah village have additional knowledge about online marketing, choosing online marketing channels that are well targeted, and the skills to operate social media as a means of marketing their products online.